2018
DOI: 10.17306/j.afs.2018.0599
|View full text |Cite
|
Sign up to set email alerts
|

Design of a solar dryer for small-farm level use and studying fig quality [pdf]

Abstract: Background. In the mountain areas of south-east Morocco, farmers are engaged in the solar drying of figs using traditional processes. However, this practice leads to losses in quality. This study aims to improve this drying method by designing and studying the performance of a natural convection solar dryer and the quality of fresh and dried figs. Materials and methods. An indirect solar dryer was designed and its performance was studied. The TSS content, moisture, firmness and morphological parameters of fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Maximum temperature and humidity were provided 40% and 26%, respectively, in this dryer by shading. This result was consistent with the findings of Noutfia et al (2018) who reported that suitable temperature and humidity for fig dryer are 40.1°C and 26.3%, respectively (Noutfia et al, 2018). In direct sun drying, the climatic conditions and light intensity have a significant effect on the color of fig fruits and the color changes in this method are more than in artificial drying (Şen et al, 2017).…”
Section: Interaction Effects Of Harvesting and Drying Methods On Fruit Colorsupporting
confidence: 90%
“…Maximum temperature and humidity were provided 40% and 26%, respectively, in this dryer by shading. This result was consistent with the findings of Noutfia et al (2018) who reported that suitable temperature and humidity for fig dryer are 40.1°C and 26.3%, respectively (Noutfia et al, 2018). In direct sun drying, the climatic conditions and light intensity have a significant effect on the color of fig fruits and the color changes in this method are more than in artificial drying (Şen et al, 2017).…”
Section: Interaction Effects Of Harvesting and Drying Methods On Fruit Colorsupporting
confidence: 90%
“…Emerging nations are severely facing the crisis as a substantial part of consumable foodstuff is lost due to mutilation by pests and careless handling (Jain et al, 2019;Prakash et al, 2016). Post-harvest drying is a crucial food processing activity (Noutfia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Open sun drying is dependent on weather and has other disadvantages like deterioration of food due to the development of microorganisms, birds, animals, insects etc. Solar dryers help to solve these problems and are more efficient, uniform, and economical (Noutfia et al, 2018(Noutfia et al, , 2021Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%